Impact of corporate social responsibility on customer loyalty: Evidence from the Vietnamese jewellery industry - Ngoc Tu Tran (Cogent Business & Management, 2022)
Corporate social responsibility takes an increasingly important role for businesses and receives the attention of many people. The relationship between Corporate social responsibility and customer loyalty has been tested in many business fields. So, the study aims to determine and estimate the influence of corporate social responsibility on customer loyalty in the jewellery industry. To achieve this objective, the study uses AMOS software that supports confirmatory factor analysis and structural equation modelling (SEM) to clarify whether or how Corporate social responsibility impacts customer loyalty. The inputs to the analyses were obtained through answers from 300 respondents, which completed the survey questionnaire with a total of 22 items is utilised to collect data from customers of top jewellery companies in Vietnam. The research results emphasize the corporate social responsibility is not only useful for jewellery companies but also enhances the customers' perception that relates to some factors trust, satisfaction, and loyalty.
Keywords: M14; M31; 650; Corporate social responsibility (CSR); customer loyalty; jewellery industry; Vietnam